Studies on the Laccase‐Catalyzed Oxidation of 4‐Hydroxy‐Chalcones. Issue 11 (12th April 2019) - Grosso, Simone; Radaelli, Fabio; Fronza, Giovanni; Passarella, Daniele; Monti, Daniela; Riva, Sergio
Abstract: The laccase‐catalyzed oxidation of a series of substituted 4‐hydroxy‐chalcones has been investigated. The main isolated dimeric products were, as expected, racemic mixtures of trans ‐2, 3‐dihydrobenzofuran derivatives, always co‐eluted with an additional isomeric dimer with an open structure. The two enantiomers, as well as the co‐eluted dimeric isomer could be isolated by semi‐preparative HPLC with a chiral column and were fully characterized. Abstract :